Two-Dimensional Simulation of Linear Wave Propagation in a Suspension of Polymeric Microcapsules Used as Ultrasound Contrast Agents - Galaz-Donoso, B (Acoustical Society of America, 2011)
A generation of tissue-specific stable ultrasound contrast agent (UCA) composed of a polymeric capsule with a perfluorocarbone liquid core has become available. Despite promising uses in clinical practice, the acoustical behavior of such UCA suspensions remains unclear. A simulation code (2-D finite-difference time domain, FDTD) already validated for homogeneous particles Galaz Haiat, Berti, Taulier, Amman and Urbach, (2010). J. Acoust. Soc. Am. 127, 148-154 is used to model the ultrasound propagation in such UCA suspensions at 50 MHz to investigate the sensitivity of the ultrasonic parameters to physical parameters of UCA. The FDTD simulation code is validated by comparison with results obtained using a shell scatterer model. The attenuation coefficient (respectively, the sound velocity) increases (respectively, decreases) from 4.1 to 58.4 dB/cm (respectively, 1495 to 1428 m/s) when the concentration varies between 1.37 and 79.4 mg/ml, while the backscattered intensity increases non-linearly, showing that a concentration of around 30 mg/ml is sufficient to obtain optimal backscattering intensity. The acoustical parameters vary significantly as a function of the membrane thickness, longitudinal and transverse velocity, indicating that mode conversions in the membrane play an important role in the ultrasonic propagation. The results may be used to help manufacturers to conceive optimal liquid-filled UCA suspensions. © 2011 Acoustical Society of America.